(3CLhHI Ydi CSFdI aj GdMOjK hZjQgs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s
(3ChdgG (B:s
(3eGjbhd SjOfG GdTjN GdGeGe aJM GdOjf ai GdMOjK GdPi CNQLg GdOGQ bWfi hGdHjgbi Yf YGFTI s
(3BNQgG (B:s
(3hbO ONd gPG GdJaGhJ ai GdCTgQ ef SfI KeGf hKdGKjf hGddg JYGdi CYde , hHYOg (B: (3Ke GdLhGH Ydi GdCSFdI s
(3ef b (B61 (3Edi (B113 (3Yfi GdeDda HCSGfjOg hJQGLe TjhNgs
(3heGQhGg Yfge ef GdcJH hGdELGRGJ heG bQC Ydjge ef GdcJH hNJeg HeG QhGg Yf TjhNg ef ebWYGJ TYQjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
Keywords: (3GdJGQjNs